The Role of Neuroglial Crosstalk and Synaptic Plasticity-Mediated Central Sensitization in Acupuncture Analgesia - Zhongxi Lyu; Yongming Guo; Yinan Gong; Wen Fan; Baomin Dou; Ningcen Li; Shenjun Wang; Yuan Xu; Yangyang Liu; Bo Chen; Yi Guo; Zhifang Xu; et al. (Neural Plasticity)
Although pain is regarded as a global public health priority, analgesic therapy remains a significant challenge. Pain is a hypersensitivity state caused by peripheral and central sensitization, with the latter considered the culprit for chronic pain. This study summarizes the pathogenesis of central sensitization from the perspective of neuroglial crosstalk and synaptic plasticity and underlines the related analgesic mechanisms of acupuncture. Central sensitization is modulated by the neurotransmitters and neuropeptides involved in the ascending excitatory pathway and the descending pain modulatory system. Acupuncture analgesia is associated with downregulating glutamate in the ascending excitatory pathway and upregulating opioids, 𝛾-aminobutyric acid, norepinephrine, and 5-hydroxytryptamine in the descending pain modulatory system. Furthermore, it is increasingly appreciated that neurotransmitters, cytokines, and chemokines are implicated in neuroglial crosstalk and associated plasticity, thus contributing to central sensitization. Acupuncture produces its analgesic action by inhibiting cytokines, such as interleukin-1β, interleukin-6, and tumor necrosis factor-α, and upregulating interleukin-10, as well as modulating chemokines and their receptors such as CX3CL1/CX3CR1, CXCL12/CXCR4, CCL2/CCR2, and CXCL1/CXCR2. These factors are regulated by acupuncture through the activation of multiple signaling pathways, including mitogen-activated protein kinase signaling (e.g., the p38, extracellular signal-regulated kinases, and c-Jun-N-terminal kinase pathways), which contribute to the activation of nociceptive neurons. However, the responses of chemokines to acupuncture vary among the types of pain models, acupuncture methods, and stimulation parameters. Thus, the exact mechanisms require future clarification. Taken together, inhibition of central sensitization modulated by neuroglial plasticity is central in acupuncture analgesia, providing a novel insight for the clinical application of acupuncture analgesia.